Social Relevance and Post-stroke Epilepsy Prevention - Naydenov, Christian; Parashkevova-Simeonova, Boryana; Mancheva, Velina (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract: Stroke is an important cerebrovascular disease resulting in long-term disability and death. A rare consequence of stroke is structural epilepsy. Here we discuss the importance of post-stroke epilepsy prevention. We look into the occurrence of stroke and epilepsy in the general population, the risk factors and severity of those conditions and the significance of early seizure prevention after the stroke. We analyze published research papers and reviews dealing with this problem. In brief, there is a diagnostic problem leading to ineffective treatment. On one hand preventing seizures in patients with no history of epilepsy, treating them with medications with known side effects. On the other hand by not treating them, risk seizures and future repercussions for their health and wellbeing. Here we propose ways to select patients for treatment and refine the diagnostic considerations for early start of anti-seizure therapy.